Engineering of a kinetically driven phase of phenoxazine by surface crystallisation. Issue 27 (22nd June 2022) - Kaltenegger, Martin; Hofer, Sebastian; Resel, Roland; Werzer, Oliver; Riegler, Hans; Simbrunner, Josef; Winkler, Christian; Geerts, Yves; Liu, Jie
Abstract : Surface crystallisation yields an unknown polymorph of the phenoxazine molecule. Tuning the crystallisation conditions causes a defined crystal growth of either the thermodynamically stable phase or the kinetic phase observed exclusively within thin films. Abstract : The appearance of different polymorphs at surfaces is a well-known phenomenon for organic molecules. Here the phenoxazine molecule, a small molecule with a rather rigid conformation whose bulk crystal structure (form 1) could be solved recently, is studied. The molecule was crystallized on silicon oxide surfaces from solution by drop casting and spin coating using five different solvents. Besides the concentration ranging from 0.8 g l −1 to 50 g l −1, the evaporation rate of the solvent was also controlled. By this process a new polymorph (form 2) was found which preferably forms at high solvent evaporation rates ( e.g. by spin coating). The crystal structure was solved by combining grazing incidence X-ray diffraction with theoretical methods of packing determination based on molecular dynamics and density functional theory. Severe disorder is found within the structure of the new polymorph, similar to those known for form 1. Comparing the phases of phenoxazine with the results of the surface crystallization studies here reveals that the new phase is a kinetically driven phase of metastable character. This work shows that surface crystallization is a valuable tool to search for new polymorphs of organic molecules and to characterise them in terms of their kinetic appearance and thermodynamic stability.